2022
DOI: 10.1186/s13072-022-00439-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary adaptation of the Polycomb repressive complex 2

Abstract: The Polycomb repressive complex 2 (PRC2) is an essential chromatin regulatory complex involved in repressing the transcription of diverse developmental genes. PRC2 consists of a core complex; possessing H3K27 methyltransferase activity and various associated factors that are important to modulate its function. During evolution, the composition of PRC2 and the functionality of PRC2 components have changed considerably. Here, we compare the PRC2 complex members of Drosophila and mammals and describe their adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 141 publications
1
20
0
Order By: Relevance
“…3b ). This experiment also confirmed previous reports that EPOP predominantly interacts with the PRC2.1 class of PRC2, which consists of the Polycomb-like proteins, but lacks JARID2 and AEBP2 14-16 . Importantly, we found that the L40A mutation of the BC-box exclusively impaired the interaction with ELOB/C, while no other proteins were affected by this mutation ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3b ). This experiment also confirmed previous reports that EPOP predominantly interacts with the PRC2.1 class of PRC2, which consists of the Polycomb-like proteins, but lacks JARID2 and AEBP2 14-16 . Importantly, we found that the L40A mutation of the BC-box exclusively impaired the interaction with ELOB/C, while no other proteins were affected by this mutation ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…Together with the VHL, ELOB/C is an integral part of the cellular response to hypoxia 9,13 . ELOB/C has also been demonstrated to be associated with the PRC2-interacting protein EPOP 14-16 . This association has been implicated in the interplay between transcriptional repression by PRC2 and active transcription.…”
Section: Mainmentioning
confidence: 99%
“…The dysregulation of developmental and signaling pathways due to impaired KAT6A function is consistent with the observed defects in patients with KAT6A syndrome ( 15 ). Closer inspection of the data further revealed that KAT6A deletion influences the gene expression pattern, similar to a pattern after deletion of the PRC2 core component SUZ12 ( 35 , 67 ). Namely, genes that were downregulated upon SUZ12 deletion were mostly downregulated in KAT6A KO cells, as well ( Supplementary Figure S3D, E ).…”
Section: Resultsmentioning
confidence: 72%
“…TEs are marked with DNA and H3K9 methylation that are associated with silencing in flowering plants 5 , animals, and fungi 6 . Yet, in distantly related eukaryotes TEs are instead marked by H3K27me3 deposited by the Polycomb Repressive Complex 2 (PRC2) [7][8][9][10][11] , an epigenetic mark associated with gene silencing in multicellular eukaryotes [12][13][14][15] . It was therefore proposed that the ancestral activity of PRC2 was the deposition of H3K27me3 to silence TEs 16 .To test this hypothesis we obtained mutants deprived of PRC2 activity and used genomics to analyze the role of PRC2 in extant species along the lineage of Archaeplastida.…”
mentioning
confidence: 99%